2011
DOI: 10.1590/s0034-71672011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Aborto provocado e violência doméstica entre mulheres atendidas em uma maternidade pública de Salvador-BA

Abstract: ReSUmOEstudo quantitativo, com o objetivo de estudar a violência doméstica em mulheres em situação de aborto provocado. Foram entrevistas 147 mulheres internadas por aborto provocado numa maternidade pública, na cidade de Salvador-BA. Os sujeitos foram, na maioria, mulheres jovens, negras, com baixa escolaridade, dependentes economicamente dos cônjuges, que vivenciam violência psicológica, física e sexual cometida pelos cônjuges. Quase metade das mulheres vivenciou violência doméstica durante a gravidez atual,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
0
10
0
13
Order By: Relevance
“…This is a reality in women's lives that relates to abusive partners (9) . Studies (22)(23) show that women who experience various forms of IPV before and/or during pregnancy have a greater chance of performing unsafe abortions. This practice poses a risk to the woman's life, and the opportunity to compromise their mental health (2) .…”
Section: Discussionmentioning
confidence: 99%
“…This is a reality in women's lives that relates to abusive partners (9) . Studies (22)(23) show that women who experience various forms of IPV before and/or during pregnancy have a greater chance of performing unsafe abortions. This practice poses a risk to the woman's life, and the opportunity to compromise their mental health (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Diante desses sentimentos, o aborto acontece na maioria das vezes em silêncio, permeado pela culpa, desamparo e solidão, já que a sociedade recrimina o aborto e não existe espaço para que se possa falar sobre este significado 24,25 . No Brasil, a legislação só permite o aborto em poucas exceções: quando não há outro meio de salvar a vida da mulher e nas gestações resultantes de violência sexual.…”
Section: Discussionunclassified
“…The women of this study reported that the motivation for the abortion was the violence. 24 Other surveys of women suffering violence in marital relationships unveil how singular the situation is of the woman who suffers violence during pregnancy, which undermines not only her physical but also psychological integrity. The women interviewed decided to abort and expressed feelings such as guilt, fear, insecurity, sadness, shame, low selfesteem, anxiety, depression, post-traumatic stress and suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the experience of violence triggers several health problems and poses a threat to life. [24][25] The study conducted in Salvador, Bahia, Brazil identified the experience of domestic violence as a factor that interferes in the woman's decision to abort. This points to the fact that pregnancy and a future child trigger lifestyle changes in women, contributing to the loss of their autonomy, which in turn relates to the decision to abort.…”
Section: Discussionmentioning
confidence: 99%